Joint effects of social class and community occupational structure on coronary mortality among black men and white men, upstate New York, 1988–92 - Armstrong, D (BMJ Group, 2003)
Study objective: Occupational structure represents the unequal geographical distribution of more desirable jobs among communities (for example, white collar jobs). This study examines joint effects of social class, race, and county occupational structure on coronary mortality rates for men, ages 35–64 years, 1988–92, in upstate New York. Design: Upstate New York's 57 counties were classified into three occupational structure categories; counties with the lowest percentages of the labour force in managerial, professional, and technical occupations were classified in category I, counties with the highest percentages were in category III. Age adjusted coronary heart disease (CHD) mortality rates, 35–64 years, (from vital statistics and census data) were calculated for each occupational structure category. Main results: An inverse association between CHD mortality and occupational structure was observed among blue collar and white collar workers, among black men and white men, with the lowest CHD mortality observed among white collar, white men in category III (135/100 000). About two times higher mortality was observed among blue collar than white collar workers. Among blue collar workers, mortality was 1.3–1.8 times higher among black compared with white workers, and the highest rates were observed among black, blue collar workers (689/100 000). Also, high residential race segregation was shown in all areas. Conclusions: Results suggest the importance of community conditions in coronary health of local populations; however, differential impact on subpopulations was shown. Blue collar and black workers may especially lack economic and other resources to use available community services and/or may experience worse working and living conditions compared with white collar and white workers in the same communities.